Viaduct over railway next to PGE Arena in Gdansk under tests during its construction - Chróścielewski, Jacek; Miśkiewicz, Mikołaj; Pyrzowski, Łukasz; Rucka, Magdalena; Wilde, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The paper presents the in situ tests carried out during the erection of viaduct WD-1 which is a part of Trasa Slowackiego in Gdansk. Due to the unique and innovative form of the arch girder which is created by twisted pipes, the structural monitoring tests were conducted in the DIM Laboratory in the Department of Structural Mechanics and Bridge Structures at Gdansk University of Technology. The scope of tests included arch abutment measurement system, periodic control of forces in hangers during tensioning process and finally load testing.